2020
DOI: 10.3390/microorganisms8030400
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Novel Phage LPSEYT for Biological Control of Salmonella in Foods

Abstract: Salmonella is a leading cause of foodborne diseases, and in recent years, many isolates have exhibited a high level of antibiotic resistance, which has led to huge pressures on public health. Phages are a promising strategy to control food-borne pathogens. In this study, one of our environmental phage isolates, LPSEYT, was to be able to restrict the growth of zoonotic Salmonella enterica in vitro over a range of multiplicity of infections. Phage LPSEYT exhibited wide-ranging pH and thermal stability and rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…S. enterica is a pathogenic bacterium, often revealing antibiotic resistance, infecting human and animal gastrointestinal tracts; thus, development of phage therapy against this bacterium is desirable. Phages infecting Salmonella strains can also be used in controlling this bacterium in poultry [ 9 ], as well as in food protection and dishwashing procedures [ 2 , 12 , 45 ]. However, each of the abovementioned applications require different properties of phages, like various optimal growth temperatures or resistance to different pH conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. enterica is a pathogenic bacterium, often revealing antibiotic resistance, infecting human and animal gastrointestinal tracts; thus, development of phage therapy against this bacterium is desirable. Phages infecting Salmonella strains can also be used in controlling this bacterium in poultry [ 9 ], as well as in food protection and dishwashing procedures [ 2 , 12 , 45 ]. However, each of the abovementioned applications require different properties of phages, like various optimal growth temperatures or resistance to different pH conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Other serotypes may vary depending on such factors as economy and the geography of a specific region [ 11 ]. As detection of S. enterica serotypes Typhimurium and Enteritidis results in many countries in immediate liquidation of the flock and legal restrictions are pushing towards prohibiting the use of antibiotics in farming animals, alternative methods of treatment—phages, in this case—are being tested for animal and food protection [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phage genomic DNA was isolated and purified as previously described by Yan et al [ 41 ]. Briefly, 1 mL lysate with a high titer (>10 10 PFU/mL) of purified phage was used for DNA isolation.…”
Section: Methodsmentioning
confidence: 99%
“…The proposal of the use of phage therapy to treat Salmonella infections has been published previously in many reports. Those studies led to determination of properties of various Salmonella -specific phages [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], effects of application of phages to poultry [ 22 , 23 , 24 , 25 , 26 , 27 ], and results of experimental use of phages in therapies of infected animals [ 28 , 29 , 30 , 31 , 32 ]. In addition, economic analyses of potential use of anti- Salmonella phage therapy in poultry have also been published [ 1 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, economic analyses of potential use of anti- Salmonella phage therapy in poultry have also been published [ 1 , 33 ]. Despite promising results of these studies, it was also indicated that most phages infecting S. enterica have a relatively narrow host range, specific to one or a few serovars or strains [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 34 ]. Thus, characterization of newly isolated bacteriophages infecting this bacterium is reasonable.…”
Section: Introductionmentioning
confidence: 99%